Analysis of Sustainable Tourism Development at Huangdu Dong Ethnic Cultural Village in China - Wei, Li; Khan, Naimat Ullah (Journal of Marketing Development and Competitiveness, 2018)
Huangd皇都 Dong 侗族 Ethnic Cultural Village has been developing tourism for over 20 years, however, it still has some management and economic issues to be solved. This study aims at evaluating the feasibility of sustainable soft tourism development at the selected area. It probes into the elements of tourism anatomy, explores the social-economic feasibility, and analyzes the financial feasibility at the village. The gained results show that only the rich ethnic cultural resources are not a guarantee for sustainable tourism development, but there also other factors which influence the outcome as: community participation, marketing mechanism, governance strategies etc.